Interaction of Tetra-iodophenolsulphonphthalein with Proteins - MEI, HOU-DONG; LIU, XIANG-HU; QIAN, YAN; GAO, HONG-WEN (Asian Journal of Chemistry, 2010)
The formation of microelectrostatic fields in proteins is proposed and it causes the aggregation of stain. We have studied the interaction of tetra-iodophenolsulphonphthalein (TIPST) with two proteins: bovine serum albumin (BSA), ovalbumin (OVA) and Iysoxyme (LYS). Results showed that the adsorption ratios of BSA, OVA and LYS are 10.5-8.00, 0.72-0 .64 and 0.81-0.64, respectively and their adsorption constants KBSA-TIPST = 3.34 x 105-2.18 x 105, KOVA-TIPST = 1.50 x 105- 1.05 x 105 and KLYS-TIPST = 3.25 x 104-5.34 x 104 . and their absorptivities 2.48 x 105-2.29 x 105, 2.32 x 104-2.16 x 104 and 4.55 x 104-3.79 x 104 L mole-1 cm-1 at 628 nm.